Reducing Energy Consumption in the Formaldehyde Production Process - Fauzan, O. K. Muhammad; Amalia, Ilmi Nur; Nabila, Chiera Shelgi Putri; Purdivami, Radike Zahra Aisya (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Formaldehyde is a substance that has been utilized for a long time due to its numerous benefits. This research article focuses on optimizing energy consumption in formaldehyde production from methanol using metal oxide catalysts. The Formox process is one of the main methods for formaldehyde production through the partial oxidation of methanol with metal oxide catalysts. In this process, energy released by the system is recovered and reused, making the overall energy consumption more efficient and reducing the required costs. By reducing the energy consumed in the production process, emissions released into the atmosphere will decrease, and profitability can be enhanced by lowering energy-related costs. The energy results before modification show a value of 43,030,653.8 kJ/h, while the modified system yields 26,766,429.7 kJ/h, achieving an energy efficiency improvement of 37.8%. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).